Pengaruh Media Gambar Berseri Terhadap Keterampilan Menulis Teks Prosedur Pada Peserta Didik Kelas IV SDN 33 Sawahan Kota Padang - Fatimah Rahmi Hidayati; Yesni Yenti; Adrias; Inggria Kharisma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Procedural text writing skills among elementary school students remain relatively low, particularly in constructing effective sentences and organizing sequential steps, which leads to suboptimal learning outcomes. This condition is reflected in the number of students who have not achieved the minimum mastery criteria. The purpose of this study is to determine the effect of picture series media on students’ procedural text writing skills at the fourth-grade level of SDN 33 Sawahan Padang. The study employed a quantitative approach using a quasi-experimental design with a non-equivalent control group in a post-test only format. The sample was selected through purposive sampling, consisting of class IV A as the experimental group (23 students) and class IV C as the control group (22 students). Data were collected through writing tests and observation, and analyzed using the Mann-Whitney nonparametric test after normality and homogeneity assumptions were not met. The results revealed a significant difference between the two groups with a significance value of 0.049 < 0.05. The experimental class obtained a higher mean score (92) compared to the control class (81), and a higher mean rank (26.63 vs. 19.20). These findings indicate that picture series media has a positive and significant effect on improving procedural text writing skills, particularly in organizing steps, completing text structure, and using appropriate language.